Realistic humanoid robot simulation with an optimized controller: a power consumption minimization approach - Lima, José (2010)
This paper describes a humanoid robot simulator supporting joint trajectory optimization, following accurately the real robot characteristics. The simulator, based on a rigid body simulator (Open Dynamics Engine) and an OpenGL based graphics library (GLScene), provides instant visual feedback and realistic dynamics. It allows to design and test behaviours and control methods without access to the real hardware, preventing damages in the real robot in the earlier stages of development. Having in mind the energy consumption minimization, the low level trajectory planning is discussed and experimental results are presented. The proposed methods are shown to minimize the total energy assuming two intervals of constant acceleration.